Isolation of proton transfer complexes containing 4-picolinium as cation and pyridine-2, 6-dicarboxylate complex as anion: crystallographic and spectral investigations, antioxidant activities and molecular docking studies. Issue 14 (27th January 2016) - Ansari, Istikhar A.; Sama, Farasha; Shahid, M.; Rahisuddin,; Arif, Rizwan; Khalid, Mohd; Siddiqi, Zafar A.
Abstract : Three novel proton transfer complexes have been synthesized and characterized by spectral and X-ray studies. Antioxidant activity and molecular docking is also examined for the complexes. Abstract : Three novel complexes with stoichiometry [4-pic-H][M(pda)2 ]·2H2 O [M = Cr (1 ), Fe (2 ) and Co (3 ); H2 pda = pyridine-2, 6-dicarboxylic acid and 4-pic = 4-picoline] have been prepared. The complexes (1–3 ) are characterized using elemental analysis, TGA, CV, FTIR, ESI mass, 1 H & 13 C NMR, EPR, UV Visible, fluorescence, magnetic and X-ray studies. Spectral data ascertained the bonding modes and the geometry of the complexes. Single crystal X-ray data of (2 ) and (3 ) revealed the formation of proton transfer complexes in which a proton is transferred from the H2 pda moiety to the pyridine nitrogen of 4-pic. Thermal and ESI mass data confirmed the proposed stoichiometry of the complexes. Cyclic voltammetric (CV) studies confirm the formation of M II /M III quasi-reversible redox couples in solution. The antioxidant activity of (3 ) assessed using DPPH and hydrogen peroxide assays has suggested that the present compounds may be used as potent antioxidants. Molecular docking studies performed for (2 ) and (3 ) reveal that the present complexes can efficiently bind with DNA receptor with free energy of binding (FEB) values of −314 (2 ) and −276.8 kcal mol −1 (3 ). The molecular docking studies indicated a higher binding ability of (2 ) to DNA compared to that of (3 ).